APPLICATION OF SPHEROIDIZING «CHIPS»-MASTER ALLOY ON COPPER BASE CONTAINING NANOSCALE PARTICLES OF YTTRIUM OXIDE FOR HIGH-STRENGTH CAST IRON - A. S. Kalinichenko; A. G. Slutsky; V. A. Sheinert; S. A. Lenkevich; A. N. Bely (Литьë и металлургия, 2016)
The peculiarity of the technology of obtaining high-strength cast iron is application in out-furnace treatment various inoculants containing magnesium. In practice of foundry production spheroidizing master alloys based on ferrosilicon (Fe-Si-Mg type) and «heavy» alloying alloys on copper and nickel base are widespread. The urgent issue is to improve their efficiency by increasing the degree of magnesium assimilation, reduction of specific consumption of additives, and minimizing dust and gas emissions during the process of spheroidizing treatment of liquid iron. One method of solving this problem is the use of inoculants in a compact form in which the process of dissolution proceeds more efficiently. For example, rapidly quenched granules or «chip»-inoculants are interesting to apply.The aim of present work was to study the peculiarities of production and application of «Chips»-inoculants on copper and magnesium base with additions of yttrium oxide. The principle of mechatronics was used, including the briquetting inoculants’ components after their mixing with the subsequent high-speed mechanical impact and obtaining plates with a thickness of 1–2 mm.Spheroidizing treatment of molten metal has been produced by ladle method using «Chips»-inoculants in the amount of 0.8%. Secondary graphitization inoculation was not performed. Studies have shown that when the spheroidizing treatment of ductile iron was performed with inoculants developed, the process of interaction of magnesium with the liquid melt runs steadily without significant pyroeffect and emissions of metal outside of the ladle.This generates a structure of spheroidal graphite of regular shape (SGf5). The presence in the inoculant of yttrium oxide has a positive impact on the spheroidal graphite counts and the tendency of high-strength cast iron to form «white» cast iron structure. Mechanical properties of the obtained alloy correspond to high-strength cast iron HSCI60.